Hukum Keluarga Islam ala Negara: Penafsiran dan Debat atas Dasar Hukum Kompilasi Hukum Islam di Kalangan Otoritas Agama dan Ahli Hukum - Nurlaelawati, Euis (UIN Sunan Kalijaga, 2016)
This article explores the reaction to and criticism of the reform aspects introduced in the kompilasi which have arisen among Indonesian Muslim, the ulama of two biggest Muslim organizations in particular and the legal apparatus and scholars. It addresses the issue by looking at specific questions relating to the rationales ofthe reforms. Deploying socio-historical legal approach, it displays the reform aspects, the arguments and the tendency in their criticism and debate, as well as the key concepts and interpretations of Islamthey have used. It argues that these ‘ulama have distinct and differentways of looking at the reforms, which is intersected with the general attitude of these two organizations in deducting the laws of Islam. Thisarticle stresses that the reforms have always not been accepted in their whole by Muslim society and that the Islamic rationales of the reforms have often been deemed inappropriate, demonstrating in this sense the harsh debate between the use of fiqhand Qur’anand between the use of Islamic classical law and the incorporation of adatlaw as their sources and bases. Further it shows that, although the proposal of reforms was proclaimed to be based on the societal growing needs and demands, they remained to be objects of criticism and debates from such certain groups of Muslims and legal apparatus who argued to also base their criticism on the needs of society.